Effects of Dietary Carbohydrate and Lipid Concentrations on Growth Performance, Feed Utilization, Glucose, and Lipid Metabolism in Two Strains of Gibel Carp - Li, Hongyan; Xu, Wenjie; Jin, Junyan; Zhu, Xiaoming; Yang, Yunxia; Han, Dong; Liu, Haokun; Xie, Shouqi (Frontiers in Veterinary Science, 2019)
To test the hypothesis that effects of dietary carbohydrate and lipid concentrations on growth performance, feeding utilization, glucose and lipid metabolism in gibel carp A strain may be differ from F strain, these two strain of gibel carp were fed with one of three different isonitrogenous diets: HCLL (45% carbohydrate, 2% lipid), MCML (30% carbohydrate, 8% lipid), or LCHL (15% carbohydrate, 14% lipid). After 8 weeks, the HCLL-fed fish had the highest hepatosomatic index, hepatic crude lipid levels, and triglyceride levels and lipid retention efficiency. Enhanced lipogenesis and lipid uptake potential were observed in fish fed HCLL and MCML diets. Moreover, increases in glucose transport (glut2, P = 0.003) and glycolysis (gk, P = 0.012; 6pfk, P = 0.005) in livers of both strains were induced by the high-carbohydrate diet. Genotype-specific effect was identified on plasma lipid content. Plasma triglyceride levels were also greater in the F strain than in the A strain. Furthermore, the F strain had higher levels of fatty acid β-oxidation and glycolysis compared with the A strain. Nutrient retention was affected (P < 0.05) by the interaction between genotype and diet, implied dietary carbohydrate played a vital role in lipid accumulation in gibel carp. As dietary lipids increased, the F strain exhibited better feed utilization and a higher PRE than the A strain. However, the A strain had better growth performance. Overall, the F strain had better glucose uptake, glycolysis potential, and lipid utilization ability than the A strain.